2002
DOI: 10.2337/diacare.25.7.1135
|View full text |Cite
|
Sign up to set email alerts
|

HOMA-Estimated Insulin Resistance Is an Independent Predictor of Cardiovascular Disease in Type 2 Diabetic Subjects

Abstract: OBJECTIVE -To evaluate whether homeostasis model assessment-estimated insulin resistance (HOMA-IR) is an independent predictor of cardiovascular disease (CVD) in type 2 diabetes.RESEARCH DESIGN AND METHODS -Conventional CVD risk factors (sex, age, smoking, plasma lipids, blood pressure, and metabolic control) and insulin resistance (estimated by HOMA) were evaluated at baseline in 1,326 patients with type 2 diabetes examined within the Verona Diabetes Complications Study. At baseline and after a mean follow-up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
319
4
10

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 534 publications
(352 citation statements)
references
References 54 publications
(47 reference statements)
19
319
4
10
Order By: Relevance
“…Insulin and PTH were measured by automated chemiluminescence method 0.25(OH)D was measured by HPLC method. HOMAIR was calculated from fasting insulin and fasting glucose [28].…”
Section: Methodsmentioning
confidence: 99%
“…Insulin and PTH were measured by automated chemiluminescence method 0.25(OH)D was measured by HPLC method. HOMAIR was calculated from fasting insulin and fasting glucose [28].…”
Section: Methodsmentioning
confidence: 99%
“…It has been shown that the HOMA-IR index was able to rank individuals according to insulin resistance in a similar way as the euglycemic hyperinsulinemic clamp. 16 …”
Section: Identification Of the Metabolic Syndromementioning
confidence: 99%
“…Plasma insulin concentrations were measured by radioimmunoassay. Insulin resistance was estimated by calculation of homeostasis model assessment-insulin resistance (HOMA-IR) (Bonora et al, 2002); low HOMA-IR concentrations indicate high, whereas high HOMA-IR concentrations indicate low insulin sensitivity (insulin resistance).…”
Section: Measurementsmentioning
confidence: 99%